2021
DOI: 10.1002/ange.202111993
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Difluoromethylation of Alkyl Iodides Enabled by Aryl Radical Activation of Carbon–Iodine Bonds

Abstract: The engagement of unactivated alkyl halides in copper-catalyzed cross-coupling reactions has been historically challenging,d ue to their lowr eduction potential and the slow oxidative addition of copper(I) catalysts.I nt his work, we report an ovel strategy that leverages the halogen abstraction ability of aryl radicals,t herebye ngaging ad iverse range of alkyli odides in copper-catalyzed Negishi-type cross-coupling reactions at room temperature.S pecifically,a ryl radicals generated via copper catalysis effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, Liu reported the Cu-catalyzed Negishi-type cross-coupling reactions of alkyl iodides with (DMPU) 2 Zn-(CF 2 H) 2 at room temperature for alkyl difluoromethane products, which leveraged the halogen abstraction ability of aryl radicals (Scheme 4). 35 In this work, a variety of cyclohexanes 28, 32-33, 1,3-dioxanes 29, piperidines 30-31, azepane 35, cyclopentanes 36, azetidine 37 and cyclobutanes 38-39 were all well tolerated to generate the desired difluoromethylated products in good to excellent yields. The proposed mechanism for the aryl radical-enabled, Cu-catalyzed difluoromethylation of alkyl iodides is outlined in Scheme 4.…”
Section: Guang-jian Meimentioning
confidence: 83%
“…Furthermore, Liu reported the Cu-catalyzed Negishi-type cross-coupling reactions of alkyl iodides with (DMPU) 2 Zn-(CF 2 H) 2 at room temperature for alkyl difluoromethane products, which leveraged the halogen abstraction ability of aryl radicals (Scheme 4). 35 In this work, a variety of cyclohexanes 28, 32-33, 1,3-dioxanes 29, piperidines 30-31, azepane 35, cyclopentanes 36, azetidine 37 and cyclobutanes 38-39 were all well tolerated to generate the desired difluoromethylated products in good to excellent yields. The proposed mechanism for the aryl radical-enabled, Cu-catalyzed difluoromethylation of alkyl iodides is outlined in Scheme 4.…”
Section: Guang-jian Meimentioning
confidence: 83%
“…In their report, Liu and co-workers disclosed a Cu-catalyzed Negishitype cross-coupling of alkyl iodides with difluoromethyl zinc reagent. 53 The reaction proceeded with the formation of a Cu(I)−CF 2 H species via transmetalation between copper and zinc salts. A sterically bulky aryl radical was generated by an SET process between Cu(I) and diazonium salt.…”
Section: Reactionsmentioning
confidence: 99%
“…However, the former method is limited to substrates prone to undergoing S N 2-type reactions, and the latter requires a stoichiometric amount of copper salt. In their report, Liu and co-workers disclosed a Cu-catalyzed Negishi-type cross-coupling of alkyl iodides with difluoromethyl zinc reagent . The reaction proceeded with the formation of a Cu­(I)–CF 2 H species via transmetalation between copper and zinc salts.…”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…Zhang reported that catalytic Mn2(CO)10 exhibited powerful reactivity in converting alkyl iodides to alkyl radicals under green LEDs, producing a series of valuable 4-alkyl-1,4-dihydropyridines in high yields 24 . Very recently, Liu successfully achieved the difluoromethylation of alkyl iodides with high efficiency via halogen abstraction enabled by copper catalysis, demonstrating the powerful synthetic applicability of this strategy 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, generation of aryl radical from diazonium salts requires additional equipment or technology such as thermal, photochemical, and electrochemical systems 50,[55][56][57][58] . Halogen-atom transfer (XAT) occurs to deliver a more kinetically stable aryl iodide (rate constant k = 10 9 M −1 s −1 ), resulting the forming the active alkyl radicals (Fig 1c, right) 25 . Inspired by the pioneering work on the iodine atom abstraction from the silyl methyl iodide moiety by Gevorgyan 59 , we envisioned that whether diazonium salts could serve as both "radical abstractor" from alkyl halides for the formation of alkyl radical via XAT process and nitrogen source which can undergo coupling with the "in-situ" alkyl radical to assemble diverse C(sp 3 )-N bonds (Fig 1c , left).…”
Section: Introductionmentioning
confidence: 99%